2022
DOI: 10.1007/s11837-022-05559-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Use of Gas Phase Inhibition of Hydrogen Embrittlement in Gas Transmission Pipelines Carrying Hydrogen: A Review

Abstract: This review paper introduces a research project that seeks to quantify oxygen inhibition of gaseous hydrogen embrittlement with possible application for gas transmission pipelines transporting hydrogen. And it summarizes the compelling laboratory evidence that oxygen may inhibit gaseous hydrogen embrittlement. Quantification of oxygen inhibition of gaseous hydrogen embrittlement is needed to allow evaluation of this approach to the inhibition of hydrogen embrittlement in gas transmission pipelines. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…131 According to Michler et al, 132 the partial pressure of O 2 is the dominant factor that controls embrittlement. Empirical evidence of gas inhibitors on HE is summarized in several review articles 129,133,134 which have a consensus that oxygen has a mitigation effect on HE, whereas the influence of other impurities needs further investigation.…”
Section: H Entry During Electrochemicalmentioning
confidence: 99%
“…131 According to Michler et al, 132 the partial pressure of O 2 is the dominant factor that controls embrittlement. Empirical evidence of gas inhibitors on HE is summarized in several review articles 129,133,134 which have a consensus that oxygen has a mitigation effect on HE, whereas the influence of other impurities needs further investigation.…”
Section: H Entry During Electrochemicalmentioning
confidence: 99%
“…The changes in free energy for associative adsorption of CH 4 and O 2 molecules at the Al 2 O 3 /Fe interface were calculated using the partition functions in Equations ( 12) and ( 15) under varied temperatures and pressures, and the results are shown in Figure 9. The temperature and pressure ranges were set in alignment with the operating conditions of hydrogen pipelines [70]. It can be seen that the dissociative adsorptions of both CH , is calculated as the difference between the energy of the interface with trapped H atoms and the total energy of the interface without H atoms and the H atoms [71].…”
Section: Dissociative Adsorption Of Ch4 and O2 Molecules At The đ›Œ-𝐮𝑙 ...mentioning
confidence: 99%
“…At lower values of ∆K, the corresponding FCG curves were reduced. This suggested that at a low ∆K, oxygen played a role in restraining the acceleration of fatigue crack expansion caused by hydrogen [26,27].…”
Section: Hydrogen Permeation Experimentsmentioning
confidence: 99%